Assessment of Nurses’ Knowledge and Practice Regarding Aseptic Technique procedure of Urinary Catheterization in Sulaimani, Iraq - Hussein, Dyar Mohammed; Aghaways, Ismael Hama Ameen (Sulaimani Journal for Pure and Applied Sciences, 2024)
Background: Urethral catheterization is a vital basic skill which not learnt properly will lead to numerous complications, Objectives: to assess nurses’ knowledge and practice regarding aseptic technique procedure of urinary catheterization, Materials and methods: A cross-sectional descriptive design study utilized to assess nurses’ knowledge and practice regarding aseptic technique procedure of urinary catheterization at Shar Teaching Hospital, a non-probability (convenient) sampling was used to select the study participants, the study sample included (100) nurses those working in Shar Teaching Hospital, the study was conducted from September, 2022 to July, 2023. Data were collected using a selfadministered questionnaire and observational checklist, Study instruments consist of three parts, first one the nurse information tool, which consists of questions about the demographic characteristics of the nurse, second one constructed to evaluate nurses’ knowledge about urinary catheterization. The third one consists of observational checklist about nurses’ practices related to urinary catheterization procedure, Result: the results demonstrate that statistically significant associations were found between nurses' knowledge regarding aseptic technique in urinary catheterization procedure of the study sample with years of nurses’ experience and graduation level (p-value=0.034, 0.044), Also, consequences show that no statistically significant relations were found between nurses' knowledge with all other socio demographic characteristics except gender that the results demonstrate that statistically significant associations were found between nurses' practice with nurse gender (p-value=0.034)m There was statistically significant correlation between knowledge and practice that correlation (R) value was (0.043). Conclusions: Overall, we observed at Shar Teaching Hospital that: more than half of nurses had a fair level of knowledge and practice toward urinary catheterization procedure that adhered to the published guidelines, there were significant associations between nurses' knowledge and years of nurse experience and degree, according to capacity building through training programs for knowledge and practice further about urinary catheterization is advised.
Keywords: Urinary catheter; aseptic technique nurses; knowledge; and practice